(3JPcQI Chdj GdCdHGH hGdLGeY ddYLH GdYLGHs - (3OGhO Hf YeQ GdHUjQ GdCfWGcj, J (B1008 (3g` s
(3ChdgG (B:s
(3SHMGfc eHOY ehGO GdcGFfGJ HdG eKGd SHb s
(3BNQgG (B:s
(3BNQg eHJhQ, hjfJgj CKfGA GdaUd GdSGHY aj PcQgG eG jMhL Edi ebGOjQ bGfhf GdMQb hEjGc hZSd GdHbhd, heG LhgQg GdMGQ aj XGgQg, aEfg jhQKgG GdfaN s
(3HBNQgG ChQGb aj GdWdSeGJ hGdMQha hGdLOGhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B47 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B276 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs